Characterization of the procoagulant phenotype of amniotic fluid across gestation in rhesus macaques and humans - Chih Jen Yang; Lyndsey E. Shorey-Kendrick; Cristina Puy; Ashley E. Benson; Phillip A. Wilmarth; Ashok P. Reddy; Keith D. Zientek; Kilsun Kim; Adam Crosland; Chaevien S. Clendinen; Lisa M. Bramer; Olivia L. Hagen; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Amniotic fluid (AF) plays a key role in fetal development, yet the evolving composition of AF and its effects on hemostasis and thrombosis are poorly understood. Objectives: To characterize the procoagulant properties of AF as a function of gestation in humans and nonhuman primates. Methods: We analyzed the proteomes, lipidomes, and procoagulant properties of AF obtained by amniocentesis from rhesus macaque and human pregnancies at gestational age-matched time points. Results: When added to human plasma, both rhesus and human AF accelerated clotting time and fibrin generation. We identified proteomic modules associated with clotting time and enriched for coagulation-related pathways. Proteins known to be involved in hemostasis were highly correlated with each other, and their intensity of expression varied across gestation in both rhesus and humans. Inhibition of the contact pathway did not affect the procoagulant effect of AF. Blocking tissue factor pathway inhibitor reversed the ability of AF to block the generation of activated factor X. The prothrombinase activity of AF was inhibited by phospholipid inhibitors. The levels of phosphatidylserine in AF were inversely correlated with clotting time. AF promoted platelet activation and secretion in plasma. Conclusion: Overall, our findings reveal that the addition of AF to plasma enhances coagulation in a manner dependent on phospholipids as well as the presence of proteases and other proteins that directly regulate coagulation. We describe a correlation between clotting time and expression of coagulation proteins and phosphatidylserine in both rhesus and human AF, supporting the use of rhesus models for future studies of AF biology.